IMPACT OF E-LEARNING ON THE ACADEMIC PERFORMANCE OF UNIVERSITY STUDENTS - Wong Poh Kei,; Lim Kong Teong, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
E-learning has recently grown in importance and usage among educational institutions worldwide due to the expansion of internet technology. Web-based learning, online learning, dispersed learning, computer-assisted education, and internet-based learning are all used to describe e-learning. E-learning is an online learning platform that gives users, or students access to information or expertise. Because e-learning is intangible and digital, poor time management, the learning model's newness and the lack of physical monitoring of students' progress can lead to university students failing academically. Thus, this study aims to determine the effect of e-learning on students' academic performance. A quantitative survey-based research approach is used in this study. The populations in this study are STML final-year students in UUM. The methodology used a quantitative questionnaire type of Google form with a total sample of 150 people. A Google form survey was distributed via Telegram, WhatsApp, and Facebook to collect the information from respondents. The data analysis technique used in this study is Statistical Product and Service Solutions (SPSS). Based on the findings of this research, e-learning was determined by four aspects (usability, easy-to-use, quality of education system, and quality of information). The results show that e-learning has a positive relationship with academic performance. Also, the results across gender, age groups, and academic programs demonstrate no significant differences in academic performance under e-learning.